Granulomatous Gastritis Associated with Sarcoidosis: Case Report - Vedat Goral; Ragip Ortac (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Granulomatous gastritis is a condition which may occur in association with Crohn's disease, sarcoidosis, Wegener's granulomatosis, tuberculosis, foreign body reaction or certain drugs including cocaine. Here, we report a diagnosis of granulomatous gastritis in a sarcoidosis patient who presented with non-specifi c dyspeptic complaints.